The Peshawar Lancers - Stirling, S. M. (New York Roc Book, 2002)
On an alternate Earth irrevocably transformed by a violent spray of comets in the 1870s, the planet is controlled by two superpowers--the British Empire and Russia--who appear to be heading for a deadly showdown.
Keywords: Great Britain -- Russia -- Comets--Collisions with Earth